IMPLEMENTASI NILAI ISLAM MODERAT MELALUI PENDIDIKAN BERBASIS MULTIKULTURAL - Hapsi Alawi; Muhammad Anas Maarif (Journal of Research and Thought on Islamic Education (JRTIE), 2021)
Abstract: This article aims to describe and analyze the implementation and implications of moderate Islamic values through multicultural-based education at Baburrohmah Islamic Vocational School. The type of this research, namely qualitative research using a case study approach. Data analysis techniques are data collection, data reduction, data presentation, and conclusion drawing. The implementation of moderate Islamic values through multicultural-based education at Baburrohmah Islamic Vocational School, namely: 1) Applying an anti-violence view of life in the invitation of Islam or in learning through the principles of Ahlussunnah Wal Jama'ah An-Nahdiyin. 2) Adopting the principles of modern life and all its derivatives such as science and technology, democracy, human rights but also filtering them. 3) using rational thinking in approaching and understanding the source of Islamic teachings through inculcating morals with classical books and their own writings so that they are not liberal. 4) The use of a contextual approach in understanding the sources of Islamic teachings. The implications of implementing moderate Islamic values through multicultural-based education at Baburrohmah Islamic Vocational School, namely the creation of a moderate character in students inside and outside and at the time of taking and at the end of their education at the institution.Keywords: Moderate Islam, Multicultural Education, and Learning Implementation.